Edukasi Keterampilan Keperawatan Dasar Dalam Perawatan Luka Ringan Bagi Ibu Rumah Tangga Di Wilayah Pedesaan Desa Sagu Flores Timur - Hoda, Ferdinandus Suban; Banin, Servasius Ratu (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Minor wound care is a basic nursing skill that is important for the community, especially housewives in rural areas with limited access to healthcare services, to master. This community service activity aimed to provide education and training in minor wound care skills to housewives in Sagu Village, East Flores, on February 13, 2025. Implementation methods included counseling, live demonstrations, and independent practice with supervision from healthcare workers. The results of the activity demonstrated an increase in participants' understanding of hygiene principles, the use of simple materials for wound cleaning, and correct dressing techniques. This education is expected to increase community independence in treating minor wounds, thereby reducing the risk of infection and complications.